A virtual team collaboration model using network simulators to develop cybersecurity competency for higher education students - Nongnuch, Krommavut; Tasatanattakool, Pinyaphat; Kasetrattanachai, Suthin; Piriyasurawong, Pallop (Edelweiss Applied Science and Technology, 2025)
This research aims to improve and evaluate a virtual team collaboration model using network simulators to develop cybersecurity competency for higher education students. Conducting artificial research, designing, and assessing the feasibility of the virtual team collaboration model using network simulators to develop cybersecurity competency for higher education students through a process according to a conceptual framework model divided into six steps: 1) Preparation: Student HE is a group of higher education students. Virtual Team is building a team for learning and dividing educational duties as planned. Network Simulator is a program for educational use offline or online. 2) Studying the incidents of cyber threats, narratives, missions, and purposes within the team to identify conditions, skills, knowledge, and learning styles. 3) Pre-test assessment. 4) Studying how to prevent cyber threats from previous cyber threat incidents—learning how to act according to the teamwork plan to improve competency (KSA) while measuring team performance. 5) Post-test assessment. 6) Applying the results to improve cyber threat incidents, narratives, missions, and purposes. The evaluation results of the model's feasibility from experts found that the virtual team collaboration model using network simulators to develop cybersecurity competency for higher education students is at an excellent level. The model can be incorporated into the coursework of higher education students to improve cybersecurity competency.